2006
DOI: 10.1007/s11258-006-9119-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns in seed bank and vegetation of semi-natural mountain meadows

Abstract: Soil seed bank composition and vegetative spatial patterns were studied in four mountain meadow communities in the Broto Valley (N. Spain), in order to analyse the differences that might exists between the two life forms. Soil and vegetation samples were taken at 1 m intervals from 10 m  10 m quadrats in each meadow in one-year study. The spatial distribution of species was analysed along with the calculation of an autocorrelation coefficient which takes account of the relative position of samples: (Moran's I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Bonet and Pausas 2004). The main dispersal strategies were derived from field observation, and the literature data (Valbuena 1995;Bonet and Pausas 2004;Gondard et al 2006;Reiné et al 2006). To simplify the analysis, where a species exhibited more than one dispersal strategy, only the main strategy was used.…”
Section: Discussionmentioning
confidence: 99%
“…Bonet and Pausas 2004). The main dispersal strategies were derived from field observation, and the literature data (Valbuena 1995;Bonet and Pausas 2004;Gondard et al 2006;Reiné et al 2006). To simplify the analysis, where a species exhibited more than one dispersal strategy, only the main strategy was used.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesised that organisms surviving large-scale infrequent disturbances dictate much of the initial revegetation patterns . Species have been found to form long-term persistent seed banks in mountain meadows, while absent from the established vegetation (Reiné et al 2006). On the other hand, in the long run, these xeric species are expected to disappear from mesic grasslands because mesic species such as Festuca nigrescens seem to out-compete them (Sebastià 2004).…”
Section: Recolonization After Small and Large Disturbancesmentioning
confidence: 99%
“…Such studies have demonstrated that soil seed banks tend to have aggregated distributions at fine spatial scales (e.g., Thompson 1986; but see Reiné et al 2006). While studies of forest soil seed banks in the context of stand-level disturbance are numerous (e.g., Morgan and Neuenschwander 1988;McGee and Feller 1993;Qi and Scarratt 1998;Lee 2004), beyond acknowledging the heterogeneity implicit in the large variances often associated with seed bank estimates (e.g., Morgan and Neuenschwander 1988;Qi and Scarratt 1998), coarse-scale heterogeneity in forest soil seed bank species composition has received little attention.…”
Section: Introductionmentioning
confidence: 99%